العناصر الثابتة والمتغيرة في النظم الإنشائية وأثرها على تعزيز مفهوم المرونة (Latakia University Journal -Engineering Sciences Series, 2019)
تحتوي المباني كلها في العالم على مجموعة من العناصر الرئيسة (الثابتة) التي تعمل كأرضية عمل للعناصر الثانوية (المتغيرة) ضمن كل أنواع النظم التصميمية ( إنشائي و تقني – وظيفي – اجتماعي – زمني ) ونلاحظ أن العناصر الرئيسة في المبنى هي التي تتمتع بصفة الثبات أي عدم القدرة على تغيير موقعها أو شكلها أو وظيفتها أو عمرها الافتراضي على نحو يجعل من الضروري جداً مراعاة الأسس التي توزع وتصمم هذه العناصر على أساسها بهدف تعزيز قدرة المبنى على التأقلم مع المتغيرات المستقبلية من حيث قدرته على تغيير حجم ووظائف فراغاته أو القدرة على التوسع مستقبلا أي رفع درجة مرونة المبنى من خلال التوزيع المتقن لهذه العناصر أو من حيث العمل على تطابق أماكن هذه العناصر ( كالعمل على دمج العناصر الثابتة إنشائيا كجدران القص مع العناصر الثابتة وظيفياً كعناصر الانتقال الشاقولي والأدراج مع العناصر الثابتة تقنياً كنقاط التزويد الشاقولية الخاصة بمسارات التكييف والتمديدات الكهربائية ....إلخ ) إن أمكن في التصميم المقترح . The technological revolution of the systems construction and the discovery of new technologies for reinforced concrete and metal structures, which reflected heavily on the work and experience architectural world to pose in a timely manner and significantly in the discovery and promotion of the concept of flexibility in architectural design in terms of making use of modern building systems and their ability to create large spaces able to raise the degree of flexibility in the functional spaces in buildings. The development of the construction systems led to the developed the ability of construction to bear the largest weights and to provide more spaces, and the production of new building materials such as concrete and iron allowed the opportunity to design and implement large buildings to large areas to provide modern functions to users. Construction systems are classified into fixed elements of construction and variable elements of construction; integration of fixed elements of construction with vertical movement axes provides high functional flexibility in buildings. Integration between fixed elements of construction and variable elements of construction provides high functional flexibility in buildings too.